Assessment of Product Localization during the Import Substitution in the Fuel and Energy Sector - Zhdaneev —, Oleg V. (Economy of Regions, 2022)
Considering the current geopolitical situation, the issues of technological sovereignty and fuel and energy sector development became urgent. In order to determine priorities for the implementation of public-private partnership (since these problems cannot be solved only through budgetary funding), areas largely depending on the import of equipment, technologies and software should be identified. The article presents a new methodology for assessing product localisation in the fuel and energy sector. The study reviews the existing approach (based on the Government Decree No. 719) and current challenges of implementing the local content policy in the Russian fuel and energy sector. The proposed methodology is based on the relevant experience of various countries in calculating the local content value, as well as the best practices of some Russian companies. Particular attention is paid to the complete value chain for products, services and software. The basic formula for calculating the product localisation includes estimations for each cost item in the value chain. Cost data taken from the appendix to the balance sheet, invoices and annual reports of enterprises were used as input. The total costs and import costs were considered for each cost item. According to the results of a comparative analysis of existing Russian and international methodologies, the developed approach was evaluated by the industry community and was considered to be the most relevant. The main risks of deploying the methodology in the import substitution programme, as well as risk management measures were described. The fuel and energy sector companies could use the research findings to assess the actual dependence on imported equipment and technologies.